Applicability of the Demirijian, Willems and Haavikko methods in Croatian children - Bedek, Ivan; Dumančić, Jelena; Lauc, Tomislav; Marušić, Miljenko; Čuković-Bagić, Ivana (The Journal of Forensic Odonto-Stomatology - JFOS, 2022)
Age estimation is an inescapable part of every identification process. During growth and development, it is possible to estimate age based on the developmental stages of teeth. The aim of this study was to evaluate three frequently used methods for dental age estimation on a broad sample of Croatian children. The sample comprised 1, 996 digital, standardized orthopantomograms of children (1, 121 boys and 875 girls) aged 5 to 16, collected in four major Croatian cities. Age was estimated according to the Demirjian, Willems and Haavikko methods and the accuracy of the estimation was evaluated. The Kappa for intraexaminer agreement was 0.83 for the Haavikko stages and 0.92 for the Demirjian stages. Using the Demirjian method, the average overestimation of age was 0.80 years for boys and 0.84 years for girls. The Willems method overestimated the mean age by 0.41 years in boys and 0.22 years in girls. The Haavikko method underestimated the mean age by 0.60 years in boys and 0.80 years in girls. The Willems method proved to be the most accurate and can be used for dental age estimation among Croatian children. The Demirjian and Haavikko methods showed greater deviation between dental and chronological age and require adaptation when used in the Croatian population.